Sistem Pemidanaan Terhadap Anak yang Melakukan Tindak Pidana (Lex Jurnalica, 2013)
AbstractKids as one of the human resources and is the next generation, it should receive special attention from the government, in order to develop the child to realize a strong human resources and quality. Every country in the world where this is required to provide adequate care and protection for children's rights, which among others, civil rights, economic, social and cultural rights. But it seems the position and rights of the child, if viewed from the perspective of jurisdiction has not received serious attention by the government, law enforcement and the community at large and are still far from what really should be given to them. If a child committing a crime then returned to their parents or handed over to the government, but in the form of Restorative justice, a focus on shape recovery and deliberation between the perpetrator and the victim, so mengeepankan best interests of the child.Keywords: children, criminalization system, restorative justiceÂ AbstrakAnak sebagai salah satu sumber daya manusia dan merupakan generasi penerus bangsa, sudah selayaknya mendapatkan perhatian khusus dari pemerintah, dalam rangka pembinaan anak untuk mewujudkan sumber daya manusia yang tangguh serta berkualitas. Setiap Negara dimanapun di dunia ini wajib memberikan perhatian serta perlindungan yang cukup terhadap hak-hak anak, yang antara lain berupa hak-hak sipil, ekonomi, sosial dan budaya. Namun sepertinya kedudukan dan hak-hak anak jika dilihat dari prespektif yuridis belum mendapatkan perhatian serius baik oleh pemerintah, penegak hukum maupun masyarakat pada umumnya dan masih jauh dari apa yang sebenarnya harus diberikan kepada mereka. Jika seorang Anak melakukan tindak pidana maka dikembalikan kepada orang tuanya atau diserahkan kepada pemerintah, namun dalam bentuk Restorative justice, lebih menitikberatkan pada bentuk pemulihan dan musyawarah antara pelaku dan korban, sehingga mengeepankan kepentingan yang terbaik bagi anak.Kata kunci: anak, sistim pemidanaan, restorative justice